Isolation and Analysis of Characteristic Compounds from Herbal and Plant Extracts (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Herbal and plant extracts show diverse activities and have been used for centuries as natural medicines for many health problems and diseases. Through the isolation and analysis of the compounds in the extracts, it is possible to understand why the extracts exhibit those activities, as well as the chemical metabolism of compounds that occur in plants and herbs. Recently, there have been increasing attempts to develop herbal and plant extracts into functional foods and drugs, but the legal requirements are becoming stricter. We need sophisticatedly defined extracts through the isolation and analysis of compounds comprising them in order to meet the legal requirements and to pursue quality control strategies in the production of functional foods and drugs. This Special Issue Book compiled the 15 recent research and review articles that highlight the isolation, profiling, and analysis of compounds in herbal and plant extracts, as well as quality control and standardized processing strategies for extracts with characteristic compounds.